Evaluation of the antioxidant activity of blueberry ethanol extracts under microwave extraction - Liu, Chenghai; Zhao, Xinglong; Wang, Zhen; Zheng, Xianzhe; Xue, Liangliang; Liu, Chai; Chen, Zhiying; Zhang, Bingfang (International Journal of Agricultural and Biological Engineering, 2022)
Blueberry extract contains diversiform monomers of anthocyanins, whose antioxidant activity determines the functionality of anthocyanidins and the efficacy of extraction technology. The evaluation of the antioxidant activity of anthocyanidins of blueberry ethanol extracts (BEE) was investigated by considering the monomers' identification and thermal degradation in microwave-assisted extraction (MAE). Thirteen monomers of anthocyanins were identified from the extracts of blueberry under MAE, where the highest content was for cyanidin glycosides, and the lowest content was for the malvidin glycosides. The onset temperatures of degradation for anthocyanidins monomers in BEE were 41.07°C-48.50°C, and the glycoside contents of delphinidin, cyanidin, petunidin, peonidin, peonidin, and malvidin, in turn, decreased obviously. The degradation of anthocyanidins with extraction temperature improved, other than weakened, its antioxidant activities in BEE under MAE. The research results may provide valuable guidance for the antioxidant application of extracts from blueberry.Keywords: blueberry, anthocyanins, microwave-assisted extraction, extracts, monomer, antioxidant activityDOI: 10.25165/j.ijabe.20221504.7114Citation: Liu C H, Zhao X L, Wang Z, Zheng X Z, Xue L L, Liu C, et al. Evaluation of the antioxidant activity of blueberry ethanol extracts under microwave extraction. Int J Agric & Biol Eng, 2022; 15(4): 205–213.